Kyzylorda regional newspaper is in the soviet period - Yermaganbetova, Z.N. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article discusses the history of the creation and development of the Kyzylorda regional newspaper “Syr Boyi”, talks about its editors, the authors. On specific examples, the subject is analyzed, the genre identity of the materials published in it. The author of the article pays attention to what problems were covered in this publication, published in the Soviet period under the name “Lenin Zholy” (Lenin’s Way). It is noted that at one time the newspaper highlighted pressing problems of culture, art, science, agriculture. The article studies the work of the printed publication from a scientific perspective from its very first publication, periodizes and systematizes the activities of the newspaper. In conclusion, the author concludes that in the Soviet period the periodical honestly served its readers